2020
DOI: 10.5606/ehc.2020.73629
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic role of neutrophil-to-lymphocyte ratio and monocyte-to-lymphocyte ratio in patients with enchondroma and low-grade chondrosarcoma

Abstract: Cartilaginous tumors of the skeleton are amongst the most common; however, differential diagnosis remains to be a challenge. [1,2] These neoplasms range from enchondromas to chondrosarcomas with diagnostic margin being rather vague, particularly between enchondromas and low-grade chondrosarcomas where misdiagnosis may bring burdensome consequences. Currently, clinical discrimination mainly relies on location, radiologic, and pathologic properties of the tumor which yield little agreement between different clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…11 However, few studies have investigated the diagnostic values of markers of systemic inflammation in different cancers (Table 5). In non-gynecologic cancers, NLR has been suggested to predict the presence of Hodgkin lymphoma, glioma, prostate cancer, or cartilaginous tumors (enchondroma and low-grade chondrosarcoma), 10,[37][38][39][40] whereas in gynecologic cancers, we have reported on the usefulness of NLR as a diagnostic marker for the presence of EOC. 8 Kim et al described the efficacy of NLR for the preoperative diagnosis of uterine sarcomas and suggested that NLR (≥2.12) might provide a more useful and costeffective means than serum CA-125 for their preoperative differentiation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…11 However, few studies have investigated the diagnostic values of markers of systemic inflammation in different cancers (Table 5). In non-gynecologic cancers, NLR has been suggested to predict the presence of Hodgkin lymphoma, glioma, prostate cancer, or cartilaginous tumors (enchondroma and low-grade chondrosarcoma), 10,[37][38][39][40] whereas in gynecologic cancers, we have reported on the usefulness of NLR as a diagnostic marker for the presence of EOC. 8 Kim et al described the efficacy of NLR for the preoperative diagnosis of uterine sarcomas and suggested that NLR (≥2.12) might provide a more useful and costeffective means than serum CA-125 for their preoperative differentiation.…”
Section: Discussionmentioning
confidence: 85%
“…[5][6][7][8][9] Other researchers have also reported that systemic inflammatory markers have prognostic and diagnostic values in various malignancies. 10,11 However, the values of preoperative hematological parameters for the differentiation of LMS and LM have not been fully determined.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic inflammatory biomarkers such as NLR, PLR, and LMR have recently started to be used as alternatives to conventional methods in the diagnosis and management of different types of tumors. [5,[9][10][11][12][13][14][15][16][17] The use of CBC parameters in the clinical setting as screening tools in diagnosis and prognosis of musculoskeletal tumors has been gaining popularity due to the inexpensive, non-invasive, and being easy to access nature of this method. [17] There are reports showing that the number of neutrophils that produce reactive oxygen species, which induce tumor growth, angiogenesis and metastasis, is increased more around malignant tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on blood values for diagnostic and prognostic purposes have been increasing in recent years for sarcomas. [ 5 - 7 ]…”
Section: Introductionmentioning
confidence: 99%